Higher Education Internationalization and English Language Instruction. Xiangying Huo. Springer, 2020 - Chen, Qinghua (Discourse and Writing/Rédactologie)

(untitled) (Canadian Association for the Study of Discourse and Writing, 2023)
The book "Higher Education Internationalization and English Language Instruction" is an autoethnographic work that examines the intersectionality of race and language in the Canadian higher education system. Through personal stories and narratives, the author explores themes such as native-speakerism, writing centre tutoring, multicultural education, and social justice. The book makes two significant contributions: first, it amplifies the voice of racialized individuals through the application of Critical Race Theory to personal experiences and diaries, serving as a springboard for thought and an invitation to dialogues on transformation. Second, it demonstrates the potential of personal narratives to reveal ideas that are often overlooked in positivist approaches, providing insight into methodological approaches that graduate students and young researchers can adopt. The book concludes with practical implications for addressing discriminatory systems and practises in universities to promote diversity and inclusiveness. The book follows a standard format for scholarly works and provides a useful background on the internationalisation of higher education and the significance of English as a medium for multiculturalism in Canada.